Multiple urological problems in young age: a case report - MHM, Nizam; MD, Mohd Ashraf; AR, Mossadeq; Kamarulzaman, Mohd Nazli; Rahman, Mohd Nor Gohar; Z, Mahamood; S, Hassan; Y, Maya; Z, Zaidi; Z, Hasan (Universiti Sains Malaysia, 2008)
Renal stone disease has been regarded as an uncommon problem in children as compared to adult population. The incidence varies in different parts of continent. Posterior urethral valve is also regarded as uncommon urological problem in pediatric population. The incidence is about 1 per 8,000 to 25,000 life births. A combination of renal calculi, posterior uerthral valve and vesicoureteric reflux in any given case is extremely rare especially in pediatric